Science and education: modern trends - Pronin A. A., Beltikova A. A., Kashuba E. A., Liubimtseva O. A., Petrushina A. D., Krotova E. L., Tsylova E. G., Osipov N. R., Filippov M. A., Karelskaia L. P., Mlamian N. M., Ismailov O. M., Shabaev V. G., Illarionov V. A., Tikhonov V. F., Shcherbakova I. V., Satarova L. A., Popovich L. G., Nekrasov A. M., Antipova O. V., Mardanov M. V., Mardanov R. S., Khasanova A. I., Badashkeev M. V., Sysoeva E. A., Valuev O. S., Zykov M. B. (Science and education: modern trends, 2015)
in this paper the aim of the study is to determine the mechanism of involuntary acts of inhalation and exhalation in the subjects in the absence of their own efforts to create an acceleration of the torso. These accelerations created by swinging the experimenter subjects at different seesaw. The acceleration of the body, after proper calibration, measured in units of acceleration of gravity (g). The pneumogram of breathing test recorded Spirograph SMP – 21/01 – «P-D», two-axis accelerometer sensor DE-ACCM6G fastened on the belt. Synchronous data transfer to a computer with a digital multi-channel recorder «S – Recorder – E». As the subjects participated two groups of students of not sports departments: group A – 12 students who are not engaged in sports and group B – 12 students engaged in various kinds of sports, sporting level I discharge. Two experiments were performed. In the first experiment, the experimenter acceleration created by the swing man, sitting motionless with his eyes open on seesaw for 30 seconds in two modes – for small and large oscillation amplitude. In the first mode the vertical component of acceleration of the body is maintained at a low level (1.45 ± 0.05 g), and in the second mode – at high level (1,80 ± 0,10 g). Period and frequency fluctuations swings remained constant. In the second experiment, the vertical acceleration of the torso was created efforts of experimenters on the swing – balancer in random mode. For an arbitrary change in the oscillation frequency of the experimenter (for «shaking»), the values of the vertical component of the acceleration of motion of the body is randomly changed within the range 0,30 ± 0,05 g to 1,9 ± 0,10 g. In the first experiment, the first swinging mode (low acceleration) in the subjects of group A (n = 12, 100%) and group B (n = 12, 100%), the respiration rate is equal to the frequency swing. The phase shift pneumogram breathing and sine wave vertical acceleration is a significant difference in athletes only inhalation (p <0.05). The mean value of inhalation and exhalation equal to 0,11 ± 0,04 seconds, and exhalation – 0,09 ± 0,02 seconds. Students not involved in sports, of breathing phase shifts from acceleration are true and at inhalation – 0,19 ± 0,03 seconds, and exhalation – 0,14 ± 0,01 seconds (p <0.01). In the second mode swinging (large acceleration) in the subjects of group A (n = 3; 25%) and group B (n = 12, 100%) respiratory rate becomes equal to the frequency of oscillations of acceleration. It has been found that the subjects had a reciprocal relationship between the maximum value of the vertical component of acceleration and exhalation and inhalation passage at the bottom point of the swing, and between low acceleration values and inhalation and exhalation in two extreme positions of the swing. In this mode, the high values observed phase coupling of breathing with the vertical component of the acceleration of the torso. The other subjects are not involved in sports (n = 9, 75%), respiratory rate also increased with increasing acceleration, but not a multiple of the frequency of oscillations of the swing. Athlete’s phase shift breathing and sine wave vertical acceleration have no significant difference. The average value of the shifts in the inhalation equal to 0,05 ± 0,02 seconds, and exhalation approaches zero – 0,02 ± 0,01 seconds (p > 0.05). However, students not involved in sports, there have been significant shifts the phase of respiration and the vertical component of the acceleration in the direction of increasing at inhalation – 0,31 ± 0,03 seconds, and exhalation phase – 0,24 ± 0,02 seconds (p < 0.01). This increase in of breathing phase shift indicates an increase in the error management system of coordination of breathing students with increasing acceleration, unlike athletes. In the experiment with the creation of vertical acceleration on the swing – balancer students of group A (n = 12, 100%) and some students of group B (n = 3; 25%) there was no correlation of respiration and vertical acceleration. The reciprocal relationship of the phases of respiration and vertical acceleration was observed in student athletes (n = 9, 75%). The results showed that external influences, to create a variable acceleration of motion of the body influence the formation of involuntary acts of inspiration and expiration person in the absence of his own efforts. Features of this effect depend on the magnitude of the vertical component of acceleration of the body, as well as from the experience of human motion. Obviously, the development of teaching methods in physical exercises and breathing should take into account changes in the vertical component of the acceleration of the body in these exercises.
Keywords: гравитация; дыхание человека; качели; ускорение движения туловища; инерция; реципрокная взаимосвязь; дыхание и движение; дисперсионный анализ; human breathing; swing; acceleration of the torso; inertia; gravity; reciprocal relationship; breathing and movement; analysis of variance